Analisis Potensi Ekonomi Di Kabupaten Nunukan - Agus Tri Darmawanto; Fazra Aini (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
The purpose of this study is to determine the economic potential in Nunukan Regency, North Kalimantan Province. The type of data in this study uses quantitative descriptive. The data used is secondary data sourced from the Central Statistics Agency of Nunukan Regency. The data uses Gross Regional Domestic Product Based on Constant Prices of Nunukan Regency in 2019-2023. The analysis methods used are Location Quotient (LQ) Analysis, Shift Share Analysis, Klassen Typology Analysis. The results of the study show that the economic potential in Nunukan Regency includes the agricultural, forestry and fisheries sectors, as well as the mining and quarrying sectors. Klassen Typology Analysis shows that the sectors that are included in the advanced and rapidly growing category are the agricultural, forestry and fisheries sectors. Shift Share Analysis shows that the total net shift value (Dij) is positive, meaning that it shows economic progress and economic growth in Nunukan Regency. This is because the agricultural, forestry and fisheries sectors have the highest contribution compared to other economic sectors.